Bridging intravenous thrombolysis in patients with atrial fibrillation - Mujanovic, Adnan; Kurmann, Christoph C.; Dobrocky, Tomas; Olivé-Gadea, Marta; Maegerlein, Christian; Pierot, Laurent; Mendes Pereira, Vitor; Costalat, Vincent; Psychogios, Marios; Michel, Patrik; Beyeler, Morin; Piechowiak, Eike I.; et al. (Frontiers in Neurology, 2022)
40% of acute ischemic stroke patients treated by mechanical thrombectomy (MT) have a clinical history of atrial fibrillation (AF). The safety of bridging intravenous thrombolysis (IVT) (MT + IVT) is currently being discussed. We aimed to analyze the interaction between oral anticoagulation (OAC) status or AF with bridging IVT, regarding the occurrence of symptomatic intracranial hemorrhage (sICH) and functional outcome. Multicentric observational cohort study (BEYOND-SWIFT registry) of consecutive patients undergoing MT between 2010-2018 (n=2941). Multinomial regression models were adjusted for prespecified baseline and plausible pathophysiological covariates identified on a univariate analysis to assess the association of AF and OAC status with sICH and good outcome (90-day modified Rankin Scale score 0-2). In the total cohort (median age 74, 50.6% female), 1347 (45.8%) patients had AF. Higher admission National Institutes of Health Stroke Scale (NIHSS) score (aOR 1.04 [95% 1.02 – 1.06], per point of increase), and prior medication with Vitamin K antagonists (VKA) (aOR 2.19 [95% 1.27 – 3.66]) were associated with sICH. Neither AF itself (aOR 0.71 [95% 0.41 – 1.24]), nor bridging IVT (aOR 1.08 [0.67 – 1.75]) were significantly associated with increased sICH. Receiving bridging IVT (aOR 1.61 [95% 1.24 – 2.11]) was associated with good 90-day outcome, with no interaction between AF and IVT (p=0.92). Bridging IVT appears to be a reasonable clinical option in selected AF patients. Given the increased sICH risk in VKA patients, subgroup analysis of the randomized controlled trials should analyze whether VKA patients might benefit from withholding bridging IVT.